Progress and pathology Medicine and culture in the nineteenth century - Dickson, Melissa; Taylor-Brown, Emilie; Shuttleworth, Sally (Manchester University Press, 2020)
This collaborative volume explores changing perceptions of health and disease in the context of the burgeoning global modernities of the long nineteenth century. During this period, popular and medical understandings of the mind and body were challenged, modified, and reframed by the politics and structures of 'modern life', understood in industrial, social, commercial, and technological terms. Bringing together work by leading international scholars, this volume demonstrates how a multiplicity of medical practices were organised around new and evolving definitions of the modern self. The study offers varying and culturally specific definitions of what constituted medical modernity for practitioners around the world in this period. Chapters examine the ways in which cancer, suicide, and social degeneration were seen as products of the stresses and strains of 'new' ways of living in the nineteenth century, and explore the legal, institutional, and intellectual changes that contributed to both positive and negative understandings of modern medical practice. The volume traces the ways in which physiological and psychological problems were being constituted in relation to each other, and to their social contexts, and offers new ways of contextualising the problems of modernity facing us in the twenty-first century.